Examining Food Purchase Behavior and Food Values During the COVID‐19 Pandemic. Issue 1 (4th November 2020) - Ellison, Brenna; McFadden, Brandon; Rickard, Bradley J.; Wilson, Norbert L. W.
Abstract: The COVID‐19 pandemic has altered conceptions of "normal" globally, including food purchasing and acquisition decisions. In this paper, we surveyed a panel of 1, 370 U.S. households four times during the COVID‐19 pandemic from mid‐March to late April 2020. With this unique panel, we observe changes in food expenditures, shopping behaviors, and food values as the pandemic evolved. Our results reveal reductions in food‐away‐from‐home expenditures and increases in online grocery shopping. Food values appear to be fairly stable in the early stages of the pandemic; however, decreases in the importance of price and nutrition reveal tradeoffs households make during the pandemic.